2018
DOI: 10.3389/fbioe.2018.00029
|View full text |Cite
|
Sign up to set email alerts
|

Selective Detection of Lysozyme Biomarker Utilizing Large Area Chemical Vapor Deposition-Grown Graphene-Based Field-Effect Transistor

Abstract: Selective and rapid detection of biomarkers is of utmost importance in modern day health care for early stage diagnosis to prevent fatal diseases and infections. Among several protein biomarkers, the role of lysozyme has been found to be especially important in human immune system to prevent several bacterial infections and other chronic disease such as bronchopulmonary dysplasia. Thus, real-time monitoring of lysozyme concentration in a human body can pave a facile route for early warning for potential bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 38 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…Ultrasensitive flexible FET‐type aptasensor has been developed for the detection of CA 125 cancer marker, which is based on carboxylated multiwalled carbon nanotubes which are immobilized onto reduced graphene oxide film . Graphene‐based FET has been recently reported for the sensitive and selective detection of lysozyme protein biomarker which can be applied in the fabrication of point‐of‐care devices . Palladium nanoflower which has been decorated with graphene has been used for the FET based detection of glucose in the presence of glucose oxidase (GOx) .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Ultrasensitive flexible FET‐type aptasensor has been developed for the detection of CA 125 cancer marker, which is based on carboxylated multiwalled carbon nanotubes which are immobilized onto reduced graphene oxide film . Graphene‐based FET has been recently reported for the sensitive and selective detection of lysozyme protein biomarker which can be applied in the fabrication of point‐of‐care devices . Palladium nanoflower which has been decorated with graphene has been used for the FET based detection of glucose in the presence of glucose oxidase (GOx) .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Field-effect transistors (FETs) have attracted much attention in the biosensing community as they offer many advantages such as miniaturization, low-cost, large-scale integration capability with the existing manufacturing process as well as label-free, rapid detection and highly sensitive detection of analytes [25]. A typical FET biosensor is composed of a semiconducting channel that connects the source and the drain electrodes.…”
Section: Microfluidic Aptasensors Based On Field-effect Transistors (mentioning
confidence: 99%
“…Among several 2D materials, graphene has been the most widely used as a promising FET channel material due to its superior physical, chemical, electronic properties as well as its ability to be grown in large areas with high fidelity. For example, a graphene field-effect transistor (GFET) has been employed as a biosensor for detecting DNA [62], triphosphate [63], bacteria, and viruses [64,65] as well as protein biomarkers [25,66]. Integrating a GFET biosensor with a microfluidic device can produce synergistic effect from their respective advantages, further enhancing its sensing performances.…”
Section: Microfluidic Aptasensors Based On Field-effect Transistors (mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the potential toxicity of azo dyes, Food and Agricultural Organizations and the World Health Organization have strict regulations on the use of such synthetic azo dyes as food colorants. Some studies have indicated that the abnormal lysozyme levels are related to a variety of diseases such as bronchopulmonary dysplasia, diarrheal disease, conjunctivitis, and nephropathy . Nevertheless, there is a very limited study about the toxicity of tartrazine targeting the lysozyme.…”
Section: Introductionmentioning
confidence: 99%